The Effect of User Satisfaction and Experience on Consumer Loyalty: The Mediation Role of Trust in Beauty Product Consumers of Gen Z - Alfiana Citra Maharani; Ahmad Hidayat Sutawidjaya; Siti Mariam; Abdul Haeba Ramli (International Publisher (YAPENBI), 2025)
In today's digital era, online shopping behavior among Gen Z is increasing, particularly in purchasing beauty products through e-commerce platforms. However, despite high purchase rates, consumer loyalty to a single brand remains low because they easily switch to other brands. This study aims to analyze the influence of satisfaction and user experience on consumer loyalty, and to evaluate the role of trust as a bridging factor in this relationship. The study was conducted among Gen Z consumers in Tangerang Regency who had purchased beauty products through e-commerce platforms in the past six months. The results indicate that satisfaction and user experience play a significant role in building trust, which ultimately drives consumer loyalty. These findings emphasize the importance of building trust through a pleasant and satisfying shopping experience to create long-term relationships between consumers and online beauty brands.